2001
DOI: 10.4049/jimmunol.167.5.2651
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Macrophages Lack CD14 and CD89 and Consequently Are Down-Regulated for LPS- and IgA-Mediated Activities

Abstract: The intestinal mucosa normally displays minimal inflammation despite the close proximity between mucosal macrophages and lumenal bacteria. Macrophages interact with bacteria and their products through CD14, a surface receptor involved in the response to LPS, and CD89, the receptor for IgA (FcαR). Here we show that resident macrophages isolated from normal human intestine lack CD14 and CD89. The absence of CD14 and CD89 was not due to the isolation procedure or mucosal cell products, but was evident at the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
242
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(262 citation statements)
references
References 34 publications
18
242
2
Order By: Relevance
“…Recent studies demonstrate that intestinal macrophages are also poorly LPS responsive and lack CD14 (90). In this study, we have addressed the regulation of TLR2 signaling by IEC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that intestinal macrophages are also poorly LPS responsive and lack CD14 (90). In this study, we have addressed the regulation of TLR2 signaling by IEC.…”
Section: Discussionmentioning
confidence: 99%
“…Staining of lamina propria macrophages has shown that expression of TLR2 and TLR4 is low in uninflamed intestine (18). In addition, isolated lamina propria macrophages do not express CD14 and are LPS unresponsive (19). Human lamina propria dendritic cells in the intestine are difficult to isolate and characterize but functional studies suggest that intestinal dendritic cells respond to TLR3 and TLR4 ligands (Table III) (20).…”
Section: Location Location Locationmentioning
confidence: 99%
“…23,24 We therefore treated KG-1 cells with 100 nM PMA for 4 days. 25,26 where small bacterial peptide products are present. Interestingly, it has been shown that macrophages expressing triggering receptor expressed on myeloid cells-1 (TREM-1), which is a receptor on neutrophils and monocytes/macrophages involved in inflammatory responses, are under-represented in the human intestine.…”
Section: The Monocytic Kg-1 Cell Line Expresses a Functional Hpept1 Tmentioning
confidence: 99%